Kedudukan Hukum Satuan Kerja Khusus Migas Sebagai Pelaksana Kegiatan Usaha Hulu Minyak Dan Gas Bumi Bagi Tata Kelola Ketahanan Energi Nasional - Rachel Octavia Manurung; FC Susila Adiyanta; Henny Juliani (Administrative Law Department, Faculty of Law, Universitas Diponegoro, 2022)
Abstract: SKK Migas is a government agency that has the authority to carry out upstream oil and gas (oil and gas) business activities. SKK Migas plays an important role in the governance of national energy security in the oil and gas sector. SKK Migas in implementing the governance of upstream oil and gas business activities, there are several obstacles that must be faced and resolved by SKK Migas in the implementation of upstream oil and gas business activities in order to realize national energy security. The study aims to find out first, what is the legal position of the special work unit (SKK Migas) as the executor of upstream oil and gas business activities for the governance of national energy security. Second, what is the role of SKK Migas in national oil and gas governance to be able to encourage national energy security, and third is what are the obstacles and how are SKK Migas solutions in implementing governance for national energy security. This legal writing uses the use of empirical juridical methods and uses qualitative research specifications, namely research that describes, describes or describes the state of the object under study in accordance with the situation and conditions when the research was carried out. The data used are secondary data obtained through literature study by studying literature and legislation related to the problems to be discussed. This data consists of secondary data in the form of primary legal materials, secondary legal materials, and tertiary legal materials. The results of the study show that First, the Legal Position of the Oil and Gas Work Unit (SKK) is as an organizer of the management of upstream oil and gas business activities, in the sense that SKK Migas has an important role in carrying out the function of controlling and supervising upstream business activities in the oil and gas sector. Second, the national Oil and Gas Governance Policy has not yet fully led to national energy security. Third, the obstacles of SKK Migas to the Implementation of Governance for National Energy Security based on the examination of the Supreme Audit Agency of the Republic of Indonesia are policy and regulatory aspects. Keywords: SKK Oil; Energy; Upstream Oil and Gas Business; Oil and Natural Gas Abstrak: SKK Migas merupakan lembaga pemerintah yang memiliki kewenangan untuk melaksanakan kegiatan usaha hulu minyak dan gas bumi (migas). SKK Migas berperan penting dalam tata kelola ketahanan energi nasional di sektor migas. SKK Migas dalam melaksanakan tata kelola kegiatan usaha hulu minyak dan gas bumi, terdapat beberapa hambatan-hambatan yang harus dihadapi dan diselesaikan oleh SKK Migas dalam pelaksanaan kegiatan usaha hulu migas demi mewujudkan ketahanan energi nasional. Penelitian bertujuan untuk mengetahui pertama, Bagaimanakah kedudukan hukum satuan kerja khusus (SKK) Migas sebagai pelaksana kegiatan usaha hulu minyak dan gas bumi bagi tata kelola ketahanan energi nasional. Kedua, Bagaimana peran SKK Migas dalam tata kelola minyak dan gas bumi nasional untuk dapat mendorong ketahanan energi nasional, dan ketiga adalah Apa hambatan serta bagaimana solusi SKK Migas dalam implementasi tata kelola untuk ketahanan energi nasional. Penulisan hukum ini menggunakan penggunaan metode yuridis empiris dan menggunakan spesifikasi penelitian kualitatif yaitu penelitian yang mendeskripsikan, menggambarkan atau memaparkan keadaan objek yang diteliti sesuai dengan situasi dan kondisi ketika penelitian tersebut dilaksanakan. Data yang digunakan yaitu data sekunder yang diperoleh melalui studi pustaka dengan mempelajari literatur dan perundang-undangan terkait dengan permasalahan yang akan dibicarakan. Data ini terdiri dari data sekunder yang berupa bahan hukum primer, bahan hukum sekunder, dan bahan hukum tersier. Hasil Penelitian menunjukkan bahwa Pertama, Kedudukan Hukum Satuan Kerja (SKK) Migas adalah sebagai penyelenggaraan pengelolaan kegiatan usaha hulu minyak dan juga gas bumi, dalam artian SKK Migas mempunyai suatu peranan penting dalam hal melaksanakan fungsi pengendalian dan pengawasan kegiatan usaha hulu di bidang migas. Kedua, Kebijakan Tata Kelola Minyak dan Gas Bumi nasional belum sepenuhnya menuju ketahanan energi nasional. Ketiga, Hambatan SKK Migas Guna Implementasi Tata Kelola Untuk Ketahanan Energi Nasional berdasarkan pemeriksaan Badan Pemeriksa Keuangan RI adalah aspek kebijakan dan regulasi. Kata Kunci: SKK Migas; Energi; Usaha Hulu Migas; Minyak dan Gas Bumi